Efficient Manufacturing & Logistics in Indian E- Commerce Industry and Its Effect on Customer Satisfaction (International Journal of Scientific Research and Management (IJSRM), 2021)
In this paper, the topic “Efficient manufacturing and logistics in Indian e-commerce industries and its effect on customer satisfaction” refers to one of the famous method (JIT - Just in time) used in manufacturing along with labor, material, and other inputs. The JIT role in Indian ecommerce industry is increasing, and awareness of Indian e-commerce industry enhances productivity of online retailers. It generates high level of satisfaction in customers, availing offline as well as online e-commerce services. JIT also contributes in improving physical distribution quality. Internal and external environment affects logistics and supply chains. From customer point of view, demand fulfillment using JIT method, clarity of production planning, sourcing and logistics are vital in Indian e-commerce industry